Main trends of functional bakery products market development - T. A. Shakhray; O. V. Vorobyova; E. P. Victorova (Новые технологии, 2021)
At present the problem of healthy nutrition is receiving more and more attention, therefore, functional foods that compensate for the deficiency of macro- and micronutrients, preserve and improve health, are becoming more in demand. Trends in the development of the market for functional bakery products have been analyzed. The official data of the Rosstat, EMISS, FSAEI SRICHI, information and analytical centers, legislative and regulatory acts of the Russian Federation have been the informational basis of the research. According to the Rosstat data, the output of bakery products in 2020 amounted to 5,4 million tons, of which the share of dietary products was 1%, and the share of functional (fortified) bakery products was only 0,5%. Analysis of the market for functional bakery products showed that their production is extremely unevenly distributed across the regions of the Russian Federation. The volume of production of functional (fortified) and dietetic bakery products in the total production in the Southern Federal District is below the all-Russian level – 0,44%, while in the Krasnodar Territory it is 0,74%. Analysis of the range of functional bakery products on the Russian market shows that the largest share in the consumer market is occupied by iodized bakery products with a high content of dietary fiber, enriched with vitamins and minerals. Based on the results of the analysis of the Russian consumer market of bakery products, a reasonable conclusion has been made that the segment of functional bakery products is extremely limited, and their range does not always correspond to the modern needs of the population. It has been shown that it is relevant to expand the range of functional bakery products, the use of which will provide the human body’s need for the necessary macro- and micronutrients for an active and healthy lifestyle.